2021
DOI: 10.1039/d0ta10602j
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar membrane polarization behavior with systematically varied interfacial areas in the junction region

Abstract: Left image is the relationship for the overpotential for water dissociation as a function of bipolar junction electric field whereas the right image presents micrographs and the procedure to make bipolar membranes with micropatterned interfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 79 publications
2
46
0
Order By: Relevance
“…A smooth BPM junction is mostly associated with morphological heterogeneities and poor contact due to differences in physicochemical properties of the membrane layers. In some cases, the surfaces of the outer layers of BPM can be roughened or micropatterned so that the other layer can blend in. A more efficient contact at the interface can be achieved using other techniques for BPM formation such as solution casting or by the use of bulk heterojunction structure formed by electrospinning, creating a high surface area of the ionomer layers in the IL. ,, These also ensure enhanced catalytic water dissociation beyond creating good contact at the IL, providing efficient transport of water and ions to and from the BPM interface for possible and stable operation at high current densities.…”
Section: Bpm Interfacial Structure and Morphologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…A smooth BPM junction is mostly associated with morphological heterogeneities and poor contact due to differences in physicochemical properties of the membrane layers. In some cases, the surfaces of the outer layers of BPM can be roughened or micropatterned so that the other layer can blend in. A more efficient contact at the interface can be achieved using other techniques for BPM formation such as solution casting or by the use of bulk heterojunction structure formed by electrospinning, creating a high surface area of the ionomer layers in the IL. ,, These also ensure enhanced catalytic water dissociation beyond creating good contact at the IL, providing efficient transport of water and ions to and from the BPM interface for possible and stable operation at high current densities.…”
Section: Bpm Interfacial Structure and Morphologiesmentioning
confidence: 99%
“…Thus, profiled interfaces might result in a continuous and increased contact area that could lower the overpotential needed to drive the water dissociation and ionic separation. Arges et al recently reported BPMs with profiled (micropatterned) interfaces prepared by forming patterns in the form of circular wells on the CEL of the BPMs. Such a strategy was shown to enhance the interfacial contact area by about twice that of the corresponding BPM interfaces without the micropatterns, corresponding to about 250 mV reduction of the onset potential .…”
Section: Bpm Interfacial Structure and Morphologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneously, changes in voltage values across the BPM was recorded using reference electrodes (Ag/AgCl single junction reference electrode placed in KCl solution filled in Haber–Luggin capillaries, M/s Pine Research Instrumentation, USA) placed on either side of the BPM. U diss was determined by the intercept of tangent drawn between the plateau region and water dissociation region (Figure S3b, stiff rise in current density) as reported by Balster et al 14 and Kole et al 36 Only the best performing HBM (i.e., low U diss ) from each category (highlighted with red color in Figure 2) were selected for understanding greater details about their morphology (surface/cross section), water uptake (WU)/swelling ratio, stability (thermal, mechanical, chemical, and operational) and acid/base generation performance.…”
Section: Methodsmentioning
confidence: 99%
“…The performance of HBM is evaluated based on the potential needed for water dissociation, which may be expressed either (i) based on the onset potential (U diss , also popularly denoted as V diss or U LCD ), or (ii) based on the potential noted with a chosen input current density (e.g., U 50 , indicates potential measured at 50 mA·cm −2 ). The I‐V characteristics of each BPM (equilibrated in test solution, 0.5 mol⋅L −1 NaCl for 24 h) was separately estimated as per method described in literatures, 35,36 by fixing it in a test cell with four‐electrode arrangement as shown in Figure S3a. Both compartments were filled with 0.1 L of test solution and stirred uniformly using mechanical stirrer.…”
Section: Methodsmentioning
confidence: 99%